Fibrinolysis in neoplastic process - Roszkowski, Krzysztof; Ziółkowska, Ewa (Contemporary Oncology/Współczesna Onkologia, 2005)
Clinical observation of the course of neoplastic diseases have recently delivered a lot of information about the pathogenetic relationship of the tumor and the hemostasis system. Interaction of the neoplastic tumor and the patient’s organism may demonstrate the hypercoagulability of blood, changes in the nature of hemorrhagic diathesis together with disorders of the fibrinolysis system. Main components in the fibrinolysis activation include plasminogen, tissue plasminogen activator (tPA), urokinase plasminogen activator (uPA), urokinase plasminogen activator receptor (uPAR), and plasminogen activator inhibitors-1 and -2 (PAI-1, PAI-2). These components are subject to extensive regulation and interactions with, for example, cellular adhesion molecules. The urinary-type plasminogen activator (uPA) controls matrix degradation through the conversion of plasminogen into plasmin and is regarded as the critical trigger for plasmin generation during cell migration and invasion, under physiological and pathological conditions (such as cancer metastasis). The proteolytic activity of uPA is responsible for the activation or release of several growth factors and modulates the cell survival/apoptosis ratio through the dynamic control of cell-matrix contacts. The urokinase receptor (uPAR), binding to the EGF-like domain of uPA, directs membrane-associated extracellular proteolysis and signals through transmembrane proteins, thus regulating cell migration, adhesion and cytoskeletal status. However, recent evidence highlights an intricate relationship linking the uPA/uPAR system to cell growth and apoptosis.